Comparing Japanese and US Language Spaces: A Case Study - Elizabeth Lavolette; Matthew Claflin (Studies in Self-Access Learning Journal)
Language spaces worldwide have much in common. However, we believe that there is a meaningful difference between spaces that are considered “language centers” in the US (USLCs) and “self-access language centers” (SALCs) in Japan. These differences provide an opportunity for practitioners and scholars involved in language spaces to learn from each other. In the current article, we investigated the Global Commons at Kyoto Sangyo University for the characteristics of both USLCs and SALCs by collecting information about it from publicly available sources and from interviews with staff. We show that it can be considered an administrative SALC (Mynard, 2019) and show how it fulfills some of the USLC mandates (Lavolette, 2018) but not others. We discuss the implications of these characterizations, including how the Global Commons could be more useful to its stakeholders. Based on this case study, scholars of both SALCs and LCs can gain new ideas for services and roles that will benefit their stakeholders and facilitate change.